2020
DOI: 10.1016/j.dam.2020.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Letter graphs and geometric grid classes of permutations: Characterization and recognition

Abstract: In this paper, we reveal an intriguing relationship between two seemingly unrelated notions: letter graphs and geometric grid classes of permutations. An important property common for both of them is well-quasi-orderability, implying, in a non-constructive way, a polynomial-time recognition of geometric grid classes of permutations and k-letter graphs for a fixed k. However, constructive algorithms are available only for k = 2. In this paper, we present the first constructive polynomial-time algorithm for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Note that in the proof of this result, we are able to use the same word to encode both the permutation π ∈ Geom(M ) and the letter graph satisfying Γ D (w) ∼ = G π . Theorem 5.5 (Alecu, Lozin, de Werra, and Zamaraev [6,7]). If the permutation class C is geometrically griddable, then the corresponding graph class G C has bounded lettericity.…”
Section: Encoding Geometric Grid Classesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that in the proof of this result, we are able to use the same word to encode both the permutation π ∈ Geom(M ) and the letter graph satisfying Γ D (w) ∼ = G π . Theorem 5.5 (Alecu, Lozin, de Werra, and Zamaraev [6,7]). If the permutation class C is geometrically griddable, then the corresponding graph class G C has bounded lettericity.…”
Section: Encoding Geometric Grid Classesmentioning
confidence: 99%
“…Instead of trying to choose one geometric gridding for each member of a geometric grid class, we seek only to show that certain griddings are geometric. Returning to this goal, the easier direction of Theorem 1.1-which states that the graph class associated to a geometrically griddable permutation class has bounded lettericity-has already been proved in [6,7], but we include another proof here, both for completeness and because it further illustrates some ideas used in the proof of the converse. Note that in the proof of this result, we are able to use the same word to encode both the permutation π ∈ Geom(M ) and the letter graph satisfying Γ D (w) ∼ = G π .…”
Section: Encoding Geometric Grid Classesmentioning
confidence: 99%
“…In [3] and [2], we showed that a permutation class X is geometrically griddable if and only if the corresponding class G X of permutation graphs has bounded lettericity. The "only if" direction of the statement is fairly straightforward: for a permutation π with a geometric gridding by a partial multiplication matrix M , one can carefully construct a decoder D over the "cell alphabet" of M (whose letters are the non-empty cells of the M ).…”
Section: The Structural Hierarchymentioning
confidence: 99%
“…A word w such that G(D, w) ∼ = G π is then given by the encoding ϕ from Subsection 2.3. The "if" direction, shown in [2], proved to be considerably more tricky from a technical perspective. At the heart of the argument, however, is a simple idea: one first uses Theorem 5 to deduce that X is monotone griddable.…”
Section: The Structural Hierarchymentioning
confidence: 99%
See 1 more Smart Citation